Scaling enterprise AI in healthcare: the role of governance in risk mitigation frameworks - Andreea Bodnari; John Travis (npj Digital Medicine)
Abstract This perspective article examines the role of governance frameworks in mitigating risks and building trust in AI implementations within healthcare organizations. As AI technologies rapidly evolve, robust governance is essential to manage potential adverse incidents and ensure fair, equitable, and effective innovation. This article highlights key risks associated with AI deployments and proposes enhancements to enterprise AI governance to better address these challenges posed by AI and digital health innovations.